1986
DOI: 10.1007/bf01299813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatostatin and thyrotropin-releasing hormone on cholecystokinin-induced gallbladder emptying

Abstract: The effect of somatostatin (0.05 and 1.5 micrograms/kg/hr) and of thyrotropin-releasing hormone (0.1 and 1.0 microgram/kg/hr) on cholecystokinin-induced gallbladder emptying was studied in healthy volunteers by means of real-time ultrasonography. In addition, the action of increasing doses (0.05, 0.15, 0.45, and 1.35 micrograms/kg/hr) of somatostatin on resting gallbladder volume was also evaluated. Somatostatin, at the dose of 0.05 microgram/kg/hr (shown to produce blood levels similar to those measured after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Previous experiments have examined the inhibitory effect of somatostatin on gallbladder contraction due either to administration of CCK or bethanechol, or to meal ingestion or sham feeding. Gullo et al found that somatostatin non-competively inhibited the effects of CCK infusion on gallbladder contraction and suggested that somatostatin acted on a different receptor in gallbladder muscle with a contrary effect to that of CCK [5]. Fischer et al demonstrated that somatostatin was able completely to abolish the gallbladder emptying response to liquid and solid meals, and to cholinergic stimulation by bethanechol and sham feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments have examined the inhibitory effect of somatostatin on gallbladder contraction due either to administration of CCK or bethanechol, or to meal ingestion or sham feeding. Gullo et al found that somatostatin non-competively inhibited the effects of CCK infusion on gallbladder contraction and suggested that somatostatin acted on a different receptor in gallbladder muscle with a contrary effect to that of CCK [5]. Fischer et al demonstrated that somatostatin was able completely to abolish the gallbladder emptying response to liquid and solid meals, and to cholinergic stimulation by bethanechol and sham feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of gallstones is also increased in acromegalics on long term treatment with the somatostatin analogue octreotide (SMS 201-995) [3,4]. The mechanism of this effect is not known, but inhibition of gallbladder contraction by somatostatin is generally believed like the crucial mechanism [2,5]. Biliary stasis may provide the time required for the precipitation of cholesterol microcrystals from bile supersaturated with cholesterol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We used three dimensions: length (longitu dinal diameter), width (side-to-side diameter) and height (anteroposterior diameter) to calculate the vol ume on the assumption that the shape of the gallblad der approximated a solid whose sections are elliptic with the eccentricity depending on the eccentricity at the level of the maximal transverse section. The method has been described in detail in previous papers [12,13], Each subject underwent 2 tests, in random order, on 2 separate days, in the morning after an overnight fast. On one day, 6 of the 11 subjects ingested a fatty liquid meal (Colecisto test: lntermedi Medicinali Sintetici.…”
Section: Methodsmentioning
confidence: 99%
“…It was not suprising, therefore, that several groups of investigators showed that native somatostatin also inhibited GB contraction in response to food or to other cholecystokinetic stimuli [16,[39][40][41][42][43], However, in the context of GBS pathogenesis, somatostatin has other potentially important effects on the biliary system includ ing a reduction in hepatic bile How in both animals [44][45][46] and man [47,48].…”
Section: Effect Of Native Somatostatin On Meal-stimulated Immunoreactmentioning
confidence: 99%